Kingdom of the Netherlands-Netherlands : Publication of Financial Sector Assessment Program Documentation: Detailed Assessment of Observance on IOSCO Principles and Objectives of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2011)
The Netherlands Authority for Financial Markets (AFM) has developed a robust supervisory framework, which exhibits high levels of implementation of the International Organization of Securities Commissions Principles. The AFM's efforts are complemented by The NetherlandsCentral bank's (DNB) program of prudential supervision, which is reasonable and credible. Gaps in the legal framework for issuers, and on management of collective investment schemes, in the case of the DNB, have imposed limitations. Their ability to react in a swift manner to emerging risks in the financial sector is limited.